Wavelength allocation in an optical switch with a fiber delay line buffer and limited-range wavelength conversion (2009)
This paper presents an approach to evaluate the performance of an optical switch equipped with both limited-range wavelength conversion and Fiber Delay Lines to resolve contention. We propose an analytical model that allows a general behavior for the packet size distribution while the inter-arrival times are assumed to be of PhaseType and can easily be relaxed to be generally distributed if needed. As the set of reachable wavelengths is a major issue in limited-range wavelength conversion, we first focus on a simple wavelength set configuration that allows the comparison of different policies and their effect on the loss rate of the system. In addition, a linear association between the loss rate of the simple and a more complex set configuration is identified. Using this association and the results from the analytical model, we derive an approximation for the more complex case, where the interactions among adjacent wavelengths play an important role. The approximation works well for different parameter instances and is particularly useful for the mid load case, when simulations become computationally prohibitive